1984
DOI: 10.1118/1.595535
|View full text |Cite
|
Sign up to set email alerts
|

A review of normal tissue hydrogen NMR relaxation times and relaxation mechanisms from 1–100 MHz: Dependence on tissue type, NMR frequency, temperature, species, excision, and age

Abstract: The longitudinal (T1) and transverse (T2) hydrogen (1H) nuclear magnetic resonance (NMR) relaxation times of normal human and animal tissue in the frequency range 1-100 MHz are compiled and reviewed as a function of tissue type, NMR frequency, temperature, species, in vivo versus in vitro status, time after excision, and age. The dominant observed factors affecting T1 are tissue type and NMR frequency (V). All tissue frequency dispersions can be fitted to the simple expression T1 = AVB in the range 1-100 MHz, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
573
2
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,092 publications
(621 citation statements)
references
References 0 publications
43
573
2
3
Order By: Relevance
“…Especially, the ratio of the T 1 relaxation times of gray and white matter is higher at 1.5 vs. 3.0 T (Bottomley et al, 1984). Histograms of T 1 -weighted MRI data differ significantly when acquired at 1.5 vs. 3.0 T. With our T 1 -weighted MDEFT protocol, we find a ratio GMV/WMV that is in the lower range of published data (here, females: 1.062, males: 1.025) but close to data from autopsy studies (1.10, Blinkov and Glezer, 1968).…”
Section: Discussionmentioning
confidence: 90%
“…Especially, the ratio of the T 1 relaxation times of gray and white matter is higher at 1.5 vs. 3.0 T (Bottomley et al, 1984). Histograms of T 1 -weighted MRI data differ significantly when acquired at 1.5 vs. 3.0 T. With our T 1 -weighted MDEFT protocol, we find a ratio GMV/WMV that is in the lower range of published data (here, females: 1.062, males: 1.025) but close to data from autopsy studies (1.10, Blinkov and Glezer, 1968).…”
Section: Discussionmentioning
confidence: 90%
“…We used the same TEs of 90 msec for 3.0 T and 1.5 T imaging because there is controversy as to whether T2 relaxation times differ between 3.0 T and 1.5 T (13). One study concluded that T2 relaxation time is independent of the main magnetic field strength (29). However, a recent study suggested that T2 relaxation times differ between 3.0 T and 1.5 T (30).…”
Section: T Mri Of the Abdomen And Pelvis In Clinical Settingsmentioning
confidence: 99%
“…The known field strength dependence of relaxation times suggests that the spin-lattice relaxation times (T 1 ) for water in various tissues as well as blood increase and converge at higher fields [17][18][19]. Further, the induced inhomogeneous field caused by local susceptibility differences increases linearly with field strength and hence the spin-spin relaxation times (T 2 ) shorten (the likely mechanism being diffusion in local field gradients [20]).…”
Section: Relaxation Parametersmentioning
confidence: 99%